Floristic Diversity of Mangrove Restoration Area: A Case Study in Pasar Rawa, North Sumatra - Harefa, Meilinda Suriani; Nasution, Zulkifli; Tuhono, Eling; Susilowati, Arida (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
Mangrove forests are important ecosystems. However, land conversion and degradation have destroyed a significant area of mangrove. Mangrove restoration employing native species has been performed in several degraded areas, including some North Sumatra regions. However, information regarding floristic diversity in monoculture restoration areas is still limited. This research aims to analyze the floristic diversity in the mangrove restoration area, which is dominated by Soneratia alba species in Pasar Rawa Village, North Sumatra. The plotted path approach was employed for vegetation analysis in a 3-ha area in Pasar Rawa. The findings revealed that 8 (eight) species were found in the S. alba restoration area. The highest Important Value Index (IVI) in the seedling stage was found in Acanthus ilicifolius, while at the sapling and tree stages, S. alba was the highest. The highest diversity index was obtained at the sapling stage, which was 1.46 (medium), and the lowest was obtained at the tree stages, which were 0.26 (low). The result showed a new recruitment of seedlings in the research location, although the species diversity value is still lower. The appearance of new species, particularly pioneer species, in the research area indicates that natural succession processes are currently taking place. Keywords: floristic, mangrove, monospecies, restoration, Sonneratia alba